Peripheral facial nerve palsy in children with enterovirus infection - Papan, Cihan; Keeren, Kathrin; Schroten, Horst; Tenenbaum, Tobias (The pediatric infectious disease journal, 2020)
Enteroviruses are one of the leading causes of central nervous system infections, but their causative role in peripheral facial nerve palsy is unresolved. We used data from a large national Enterovirus Surveillance Database to identify cases of facial nerve palsy, showing a rate of 3.8% of patients with facial nerve palsy to have enterovirus infection.